Hyperhomocysteinemia and MTHFR Polymorphisms as Antenatal Risk Factors of White Matter Abnormalities in Two Cohorts of Late Preterm and Full Term Newborns. (10th February 2015) - Marseglia, Lucia M.; Nicotera, Antonio; Salpietro, Vincenzo; Giaimo, Elisa; Cardile, Giovanna; Bonsignore, Maria; Alibrandi, Angela; Caccamo, Daniela; Manti, Sara; D'Angelo, Gabriella; Mamì, Carmelo; Di Rosa, Gabriella
Abstract : Higher total homocysteine (tHcy) levels, and C677T and A1298C methylenetetrahydrofolate (MTHFR) polymorphisms, have been reported in preterm or full term newborns with neonatal encephalopathy following perinatal hypoxic-ischemic insult. This study investigated the causal role of tHcy and MTHFR polymorphisms together with other acquired risk factors on the occurrence of brain white matter abnormalities (WMA) detected by cranial ultrasound scans (cUS) in a population of late preterm and full term infants. A total of 171 newborns (81 M, 47.4%), 45 (26.3%) born <37 wks, and 126 (73.7%) born ≥37 wks were recruited in the study. cUS detected predominant WMA pattern in 36/171 newborns (21.1%) mainly characterized by abnormal periventricular white matter signal and mild-to-moderate periventricular white matter volume loss with ventricular dilatation (6/36, 16.6%). WMA resulted in being depending on tHcy levels( P < 0.014 ), lower GA( P < 0.000 ), lower Apgar score at 1 minutes( P < 0.000 ) and 5 minutes( P < 0.000 ), and 1298AC and 677CT/1298AC genotypes (P < 0.000 andP < 0.000 ). In conclusion, both acquired and genetic predisposing antenatal factors were significantly associated with adverse neonatal outcome and WMA. The role of A1298C polymorphism may be taken into account for prenatal assessment and treatment counseling.